2018
DOI: 10.1002/hed.25438
|View full text |Cite
|
Sign up to set email alerts
|

Massive aneurysmal bone cyst of the skull base treated with denosumab

Abstract: Background Aneurysmal bone cysts are rare, benign expansile tumors most commonly involving long bones and vertebrae in patients younger than age 20. Skull base involvement is rare. Aneurysmal bone cysts shares radiological and histological features with other bone tumors, posing a diagnostic challenge. Methods/Results We report the case of a 32‐year‐old man who presented with facial pain, epistaxis, and cranial neuropathies secondary to a massive tumor of the maxillary sinus and anterior skull base. The tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…In 2018, Asi et al [26] (a case report from the United States of America) reported a 32-year-old male patient with a massive primary ABC involving the maxillary sinus and anterior skull base. The patient had significant uncontrolled tumor-related pain and multiple progressive cranial neuropathies.…”
Section: Reviewmentioning
confidence: 99%
“…In 2018, Asi et al [26] (a case report from the United States of America) reported a 32-year-old male patient with a massive primary ABC involving the maxillary sinus and anterior skull base. The patient had significant uncontrolled tumor-related pain and multiple progressive cranial neuropathies.…”
Section: Reviewmentioning
confidence: 99%
“…To our best knowledge, 2 case series (with 9 patients each) have previously been published [18][19][20] with an additional 11 cases having been published as individual case reports [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Since the initial report of denosumab treatment in two aneurysmal bone cysts of the spine [17], the clinico‐radiologic features of denosumab‐treated aneurysmal bone cysts were described in subsequent case reports and small series [18–34]. Clinically, most patients with denosumab‐treated aneurysmal bone cysts were alive with stable disease; and no denosumab‐related mortality has been reported to date [35].…”
Section: Discussionmentioning
confidence: 99%
“…Both aneurysmal bone cyst and osteoblastoma can be treated by intralesional curettage with bone grafting or cement packing, en bloc resection, or other techniques. Off‐label use of denosumab has been reported in aneurysmal bone cyst [17–35] and osteoblastoma [36,37] in the setting of multiple local recurrences or to minimize the extent of surgery to limit the morbidity of resection.…”
Section: Introductionmentioning
confidence: 99%